Use of traditional complementary and alternative medicine for HIV patients in KwaZulu-Natal, South Africa - Ramlagan Shandir; Preez Natalie; Peltzer Karl; Fomundam Henry (BMC, 2008)
Abstract Background Traditional medicine use has been reported is common among individuals with moderate and advanced HIV disease. The aim of this cross-sectional study was to assess the use of Traditional Complementary and Alternative Medicine (TCAM) for HIV patients prior to initiating antiretroviral therapy in three public hospitals in KwaZulu-Natal, South Africa. Methods Using systematic sampling, 618 HIV-positive patients were selected from outpatient departments from three hospitals and interviewed with a questionnaire. Results TCAM was commonly used for HIV in the past six months by study participants (317, 51.3%) and herbal therapies alone (183, 29.6%). The use of micronutrients (42.9%) was excluded from TCAM since mostly vitamins were provided by the health facility. Herbal therapies were the most expensive, costing on average 128 Rand (US$16) per patient per month. Most participants (90%) indicated that their health care provider was not aware that they were taking herbal therapies for HIV (90%). Herbal therapies were mainly used for pain relief (87.1%) and spiritual practices or prayer for stress relief (77.6%). Multivariate logistic regression with use of herbs for HIV as the dependent variable identified being on a disability grant and fewer clinic visits to be associated with use of herbs, and TCAM use for HIV identified being on a disability grant, number of HIV symptoms and family members not contributing to main source of household income to be associated with TCAM use. Conclusion Traditional herbal therapies and TCAM are commonly used by HIV treatment naïve outpatients of public health facilities in South Africa. Health care providers should routinely screen patients on TCAM use when initiating ART and also during follow-up and monitoring keeping in mind that these patients may not fully disclose other therapies.